Role of supportive maintenance therapy on implant survival: a university‐based 17 years retrospective analysis. Issue 4 (22nd December 2015) - Gay, IC; Tran, DT; Weltman, R; Parthasarathy, K; Diaz‐Rodriguez, J; Walji, M; Fu, Y; Friedman, L
Abstract: Objective: The objective of this study was to determine whether professional maintenance appointments were related to a decrease on dental implant loss. Methods: We performed a retrospective review (1995–2012) of 1020 patient dental charts to collect data including a cadre of different variables such as age, gender, race, diabetes, osteoporosis, jaw location, implant dimensions and professional maintenance therapy. As a patient may have multiple implants which are correlated, we selected one random implant per patient to assure independence of observations assumption of the Cox proportional hazards regression model. Data analysis was performed using Kaplan–Meier survival curves and multivariate analysis using Cox proportional hazards regression analysis. Results: Our results demonstrate that subjects with no maintenance had the lowest cumulative survival rate as compared to subjects with regular maintenance. In a multivariate Cox regression model, regular maintenance patients had the dental implant failure rate reduced by 90% as compared to no maintenance ( P = 0.001). If patients had less than one maintenance visit per year, the failure rate was reduced by 60% as compared to no maintenance, but the difference was not statistically significant ( P = 0.08). Conclusion: From this research, we conclude that a professional administered periodontal maintenance at least on an annual basis is a critical factor for implant survival.